Prison violence and the intersectionality of race/ethnicity and gender - Kerryn E. Bell (Aktualʹnye Problemy Èkonomiki i Prava, 2018)
Objective to analyze the history occurrence and development of the problem of prison violence from the viewpoint of the intersectionality of raceethnicity and gender factors.